2001
DOI: 10.1063/1.1330748
|View full text |Cite
|
Sign up to set email alerts
|

The infrared spectrum of the O⋯H⋯O fragment of H5O2+: Ab initio classical molecular dynamics and quantum 4D model calculations

Abstract: Articles you may be interested inAnharmonic force field and vibrational dynamics of CH2F2 up to 5000 cm−1 studied by Fourier transform infrared spectroscopy and state-of-the-art ab initio calculations Quantum and classical studies of vibrational motion of CH 5 + on a global potential energy surface obtained from a novel ab initio direct dynamics approachThe gas phase IR spectrum of the O¯H¯O fragment of H 5 O 2 ϩ and its deuterated analogue are calculated using ab initio classical molecular dynamics based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
137
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(148 citation statements)
references
References 73 publications
6
137
1
4
Order By: Relevance
“…At 1 K the proton is on average displaced from its equilibrium position by only about 0.01 Å. 35 With increasing temperature, the proton displacements along the flat bottom of the potential well increase significantly, reaching up to 0.2 Å at 360 K. 35 As a result, the proton coordinates are subject to a large fluctuation that results in substantial mechanical and electrooptic anharmonicity. This is expected to significantly complicate the calculated IR spectrum.…”
Section: Bands Associated With the O-h + -O Group Vibrationsmentioning
confidence: 99%
See 2 more Smart Citations
“…At 1 K the proton is on average displaced from its equilibrium position by only about 0.01 Å. 35 With increasing temperature, the proton displacements along the flat bottom of the potential well increase significantly, reaching up to 0.2 Å at 360 K. 35 As a result, the proton coordinates are subject to a large fluctuation that results in substantial mechanical and electrooptic anharmonicity. This is expected to significantly complicate the calculated IR spectrum.…”
Section: Bands Associated With the O-h + -O Group Vibrationsmentioning
confidence: 99%
“…This is expected to significantly complicate the calculated IR spectrum. The most recent calculations (4D) of Vener et al 35 take anharmonicity into account and show coupling between all four frequencies of the shared proton. At this level of theory, the fundamental bending frequencies γ(OHO) and δ(OHO) for the free H 5 O 2 + ion are ca.…”
Section: Bands Associated With the O-h + -O Group Vibrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, an experimental measurement of the absolute intensity seems unavailable. Theoretical studies also give the relative intensities of this mode to be 3-10, 46 8, 47 and 20-40 48 times the intensity of the OH stretches of the end groups. For (CH 3 OH) 2 H + , the OH stretch at 1010 cm −1 (also 0 − ← 0 + in our notation) was computed to have an intensity of 2567 km/mol 44 .…”
Section: A Symmetric H-bondsmentioning
confidence: 99%
“…+ in the 500-2000 cm À1 region (in which the modes of the bridging proton are expected) by Asmis et al [1] has raised questions [2,3] about the assignment [4] of the observed bands and stimulated more experimental work. [3,5,6] Most recently, infrared predissociation (IRPD) spectroscopy has been applied to the complex of H 5 O 2 + with Ar, [5,6] and the spectrum obtained shows some differences to that obtained by IRMPD.…”
mentioning
confidence: 99%